Upaya Peningkatan Kecerdasan Kinestetik Melalui Permainan Lompat Katak Kelompok B 1 Di Ra An-Nisa 2 Dulang Wonokerso Kedawung Sragen Tahun Pelajaran 2014/2015 - Wadyastuti, Festi, Drs. Hasto Daryanto, M.Pd, Junita Dwi Wardhani, SE. M,Ed (2015)
The frog jumping geme is interesting and gratify for chillhood. For the reallity happned in the study in kindergarden, the activity study is monuton increase the kinesthetic intelegence the chilren only sit and don't actif to follow activity that is given by teacher, the activity is only given papper sheet. The purpose of the reasearch is increase kinesthetic intelegence, this kind of the reaceasch is Research Actifity Class (RAC) with two cycle procedure that consilt of for steps the are planned, implementation, observasion and reflection. The subject of the reseach teacher and 23 cheldren's B1. The reasearch'sresult said that with use the frog jumping game cun increas the children's kinesthetic intelegence, there are the average's mecentage of intreased children's kinesthetic intelegence befor implementation until second cycle for pre cycle 46,74%, first cycle 65,24%, and scond cycle 86,69%. The conclusion of this research is inreased for children's the kinesthetic intelegenci with frog jumping game in RA An Nisa 2 Dulang Wonokerso Kedawung Sragen academic year of 2014/2015.